2013
DOI: 10.1016/j.cep.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Control assessment for heat integrated systems. An industrial case study for ethanol recovery

Abstract: Highlights•Heat integration is needed for energy reduction but can deteriorate controllability •Soundly designed controllers can handle complex processes •The deterioration of controllability was handled by the controllers •Large energy savings are possible with a good dynamic response Abstract:Heat integration is essential for reducing the energy consumption of process industries. However, it may render the dynamic operation more interactive and difficult to control. This paper assesses the implications of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Indeed, the theoretical increment in process efficiency gained through any PI application might be compromised if the plant is difficult to control and therefore cannot be operated at its nominal operating point [7]. Traditionally, process control design has been conducted separately after the process design and usually by other experts.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the theoretical increment in process efficiency gained through any PI application might be compromised if the plant is difficult to control and therefore cannot be operated at its nominal operating point [7]. Traditionally, process control design has been conducted separately after the process design and usually by other experts.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In addition, PI processes typically involve faster and more complex dynamics (response times) [3], and it is suggested that in intensified processes, the dynamics of sensors and actuators may also play a crucial role in controller design and control performance [11,12]. In general, the higher degree of integration will make the process more challenging to control and will perhaps restrict the implementation of highly intensified processes in industry [7]. Many of the published works on control design for intensified processes deal with reactive distillation (see, e.g., [10,[13][14][15]), but reported work in the area of solids 1 http://ibd-project.eu/…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The dynamic performance of more complex distillation systems for ethanol recovery has also been studied. Mauricio-Iglesias et al [29] evaluated the influence of heat integration in the ethanol-water distillation process, showing that the energy savings are achieved at the expense of a deterioration in the process controllability. Ramírez-Marquez et al [30] analyzed the dynamic behavior of alternative separation processes for ethanol dehydration by extractive distillation, considering different intensified arrangements based on thermally coupled distillation systems.…”
Section: Introductionmentioning
confidence: 99%
“…As process control is an intrinsic part of process engineering, without a process control assessment, the target of DFSS, and new concepts, is unreachable. The theoretical increment in process efficiency gained through PI might be compromised if the plant is difficult to control and therefore cannot be operated at its nominal operating point (Mauricio-Iglesias et al 2013).…”
Section: Introductionmentioning
confidence: 99%